2015
DOI: 10.1190/int-2014-0248.1
|View full text |Cite
|
Sign up to set email alerts
|

Dual-well 3D vertical seismic profile enabled by distributed acoustic sensing in deepwater Gulf of Mexico

Abstract: We have acquired and processed 3D vertical seismic profile (VSP) data recorded simultaneously in two wells using distributed acoustic sensing (DAS) during the acquisition of the 2012 Mars 4D ocean-bottom seismic survey in the deepwater Gulf of Mexico. The objectives of the project were to assess the quality of DAS data recorded in fiber-optic cables from the surface to the total depth, to demonstrate the efficacy of the DAS VSP technology in a deepwater environment, to derisk the use of the technology for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…DAS technology enables acquisition of high-resolution seismological data at frequencies from the kHz to mHz for long distances (tens of km) and at very dense spatial samplings (down to 1 m) in contexts in which the use of conventional sensors is intricate and/or costly (Daley et al, 2016;Becker et al, 2017). DAS is incrementally being adopted in the field of applied geophysics and a variety of studies have demonstrated its suitability for a range of applications such as vertical seismic profiling (Daley et al, 2013;Mateeva et al, 2013;Wu et al, 2015;Wu et al, 2017), time-lapse monitoring of near-surface properties (Dou et al, 2017;Ajo-Franklin et al, 2019), earthquake detection (Lindsey et al, 2017;Ajo-Franklin et al, 2019;Li & Zhan, 2018), and hydrological monitoring (Becker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DAS technology enables acquisition of high-resolution seismological data at frequencies from the kHz to mHz for long distances (tens of km) and at very dense spatial samplings (down to 1 m) in contexts in which the use of conventional sensors is intricate and/or costly (Daley et al, 2016;Becker et al, 2017). DAS is incrementally being adopted in the field of applied geophysics and a variety of studies have demonstrated its suitability for a range of applications such as vertical seismic profiling (Daley et al, 2013;Mateeva et al, 2013;Wu et al, 2015;Wu et al, 2017), time-lapse monitoring of near-surface properties (Dou et al, 2017;Ajo-Franklin et al, 2019), earthquake detection (Lindsey et al, 2017;Ajo-Franklin et al, 2019;Li & Zhan, 2018), and hydrological monitoring (Becker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…; Wu et al . ). Although, many examples show that DAS has the potential to provide low‐cost reservoir monitoring (Hornman et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Wu et al . ; Zhan, Kommedal and Nahm ). This DAS‐VSP survey was the first conducted in a deepwater setting.…”
Section: Introductionmentioning
confidence: 99%
“…The data quality appears to be correlated with the cementation condition, suggesting that quality of the cementing job affects the DAS-VSP data when the behind casing method is adopted. Until the end of 2016, the most advanced DAS-VSP survey was probably the case of the deepwater Mars field in the Gulf of Mexico (Mateeva et al 2013;Wu et al 2015;Zhan, Kommedal and Nahm 2015). This DAS-VSP survey was the first conducted in a deepwater setting.…”
mentioning
confidence: 99%